Qualidade de sementes de cevada destinadas ao processo de malteação - Stormovski, Elenize Maria (2018)
The barley (Hordeum vulgare) is one of the more important grains in the world. It is mainly produced in the south region of Brazil, used for human feed, animal and mainly for the production of malt for the brewing industry, with desirable characteristics related to germinative power and protein content. The objective of this study was to evaluate the physiological and bromatological quality of different barley cultivars destined to the malting process. Two studies were conducted, the first field to produce barley cultivars: ANA 01, BRS Cauê, BRS Greta, BRS Korbel, BRS Manduri and BRS Subia and the second in the Laboratories of Sustainable Management of Agricultural Systems and Bromatology and Technology of Animal and Plant Origin Products from the Federal University of South Frontier (UFFS), Erechim Campus, to determine the physiological and bromatological quality of barley cultivars produced in the first test. The tests carried out in the laboratory were: germination, vigor, weight of one thousand seeds, hectoliter weight and determination of nutritive value, by means of the first dry matter (ASA), second dry matter (ASE), mineral matter (MM), ethereal extract (EE) and crude protein (CP). None of the cultivars produced can be destined to the brewing industry, since they did not present the minimum rates of 95% of germination and maximum content of 12% of proteins. The cultivar that approached the expected results was BRS Korbel, with germination of 82% and crude protein of 13.56%.